PENGARUH INTELECTUAL CAPITAL, GOOD CORPORATE GOVERNANCE DAN AUDIT INTERNAL TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN UKURAN PERUSAHAAN DAN LEVERAGE SEBAGAI VARIABEL MEDIASI - Yusuf Yusuf; Lukman Anthoni; Asep Suherman (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
It is important for stakeholders to know the factors that improve financial performance, because by knowing the factors that affect a company's financial performance, decision makers and future predictions by interested parties become more accurate. This research uses secondary data from the Indonesian Stock Exchange. The research population is banking issuers that have gone public during the 2016-2020 period. The collected data were analyzed descriptively and path analysis using AMOS software. The results of the study show that Intellectual Capital has a significant effect on company performance, then Intellectual Capital has a significant effect on company size and Internal Audit has a significant effect on company size, apart from this all hypotheses are rejected (not significant). Firm size and leverage are unable to mediate the influence of Intellectual Capital, Good Corporate Governance and Internal Audit on Company Performance.